NEUROTRANSMITTER AND BRAIN PARTS INVOLVED IN SCHIZOPHRENIA - Arya, Ashwani; Sindhwani, Gulshan; Kadian, Renu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Schizophrenia (SCZ) is a major debilitating, complex, and costly illness that strikes 1% of the world’s population. It is characterized by three general types of symptoms: Atypical symptoms (aggressiveness, agitation, delusions, hallucinations), depressive symptoms (alogia, avolition, anhedonia, apathy), and cognitive symptoms (impaired attention, learning, memory). The etiology of SCZ has still not been fully understood. Alteration in various neurochemical systems such as dopamine, serotonin, norepinephrine, gamma-aminobutyric acid, and glutamate are involved in the pathophysiology of SCZ. The lack of understanding regarding the exact pathogenic process may be the likely a reason for the non-availability of effective treatment, which can prevent onset and progression of the SCZ. The tools of modern neuroscience, drawing from neuroanatomy, neurophysiology, brain imaging, and psychopharmacology, promise to provide a host of new insights into the etiology and treatment of SCZ. In this review, we will discuss the role of the various neurotransmitter concerned and brain parts exaggerated in the SCZ.